2014
DOI: 10.1007/s00221-014-4020-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of local and widespread muscle fatigue on movement timing

Abstract: Repetitive movements can cause muscle fatigue, leading to motor reorganization, performance deficits, and/or possible injury. The effects of fatigue may depend on the type of fatigue task employed, however. The purpose of this study was to determine how local fatigue of a specific muscle group versus widespread fatigue of various muscle groups affected the control of movement timing. Twenty healthy subjects performed an upper-extremity low-load work task similar to sawing for 5 continuous minutes both before a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 41 publications
1
26
0
Order By: Relevance
“…Mean shoulder horizontal abductionadduction angles were significantly greater in the final minute of the task (End) than in the first minute (Start), whereas mean shoulder-elbow relative phase was significantly decreased as a function of time. These results are consistent with results from previous studies that used repetitive upper-limb tasks and that demonstrated shifts in posture and compensatory changes in coordination, interpreted as strategies to decrease the load on fatiguing muscles (Côté et al, 2002(Côté et al, , 2005Cowley et al, 2014;Forestier & Nougier, 1998;Gates & Dingwell, 2011). However, this is the first time that upper-limb coordination changes have been quantified using the continuous relative phase approach.…”
Section: Discussion Motor and Sensory Adaptations To Fatigue-inducingsupporting
confidence: 81%
See 1 more Smart Citation
“…Mean shoulder horizontal abductionadduction angles were significantly greater in the final minute of the task (End) than in the first minute (Start), whereas mean shoulder-elbow relative phase was significantly decreased as a function of time. These results are consistent with results from previous studies that used repetitive upper-limb tasks and that demonstrated shifts in posture and compensatory changes in coordination, interpreted as strategies to decrease the load on fatiguing muscles (Côté et al, 2002(Côté et al, , 2005Cowley et al, 2014;Forestier & Nougier, 1998;Gates & Dingwell, 2011). However, this is the first time that upper-limb coordination changes have been quantified using the continuous relative phase approach.…”
Section: Discussion Motor and Sensory Adaptations To Fatigue-inducingsupporting
confidence: 81%
“…Moreover, different kinds of fatigue protocols have led to increases in motor variability (Cowley, Dingwell, & Gates, 2014;Fuller et al, 2009;Gates & Dingwell, 2011;Qin, Lin, Faber, Buchholz, & Xu, 2014). Motor variability, defined as the intrinsic variability in actions controlled by the sensorimotor system (Madeleine, 2010;Mathiassen, Möller, & Forsman, 2003), has evolved into an important concept in the field of biomechanics because of the proposed benefit of variability toward decreasing the rate of fatigue development and the relative risk of injury (Côté, 2014;Madeleine, 2010;Srinivasan & Mathiassen, 2012).…”
mentioning
confidence: 99%
“…However, a significant degradation was observed immediately after 5 hr, but this performance decrement was no longer present after the recovery period. Several studies have illustrated motor control impairments induced by muscle fatigue (Cowley, Dingwell, & Gates, 2014; Johnston, Howard, Cawley, & Losse, 1998; Selen, Beek, & van Dieen, 2007). However, these effects were measured only immediately after a rather severe fatiguing task regimen (at least 7 on a 10-point subjective rating scale).…”
Section: Discussionmentioning
confidence: 99%
“…The mean IMPF value was obtained for each movement cycle of the fatigue protocol. The rate of decrease in frequency was calculated using the average IMPF from each cycle [ 6 ]. The IMPF was expected to decrease because muscle fatigue causes motor units to contract more synchronously leading to a decrease in high frequencies in the EMG signal [ 27 , 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…Many factors influence the way that people change their movement patterns after fatigue. In particular, fatigue that is localized in a specific muscle group causes greater changes in muscle coordination [ 5 ] and movement amplitude and speed [ 6 ] compared to fatigue that is widespread over several muscles. The direct relationship between muscle fatigue, movement, and injury is difficult to discern because the conditions that lead to fatigue and the activities performed while fatigued vary across worksites.…”
Section: Introductionmentioning
confidence: 99%